Quality Characteristics of Purslane (Portulaca oleracea L.) Leaf and Stem Powder-Supplemented Cupcakes - Muhammad Younis; Khurram Afzal; Muhammad Tauseef Sultan; Roshina Rabail; Saeed Akhtar; Tariq Ismail; Muhammad Usman Khalid; Muhammad Asim Shabbir; Rana Muhammad Aadil (Journal of Food Quality, 2023)
The current research focused on improving the nutritional quality of cupcakes by using micronutrient-rich vegetables, specifically purslane’s leaves and stems. The purslane leaves and stems were sun-dried and analyzed for their proximate, mineral, and antioxidant potential. After conducting preliminary trials, flour blends supplemented with purslane powders ranging from 2 to 4% were evaluated for their rheological behavior and suitability in bakery cupcakes. The results indicated that purslane leaves and stems are a rich source of crude proteins (18.04 ± 0.61 and 15.62 ± 1.63%, respectively) and mineral contents, especially iron contents (214.28 ± 123.13 and 243.37 ± 5.25 mg/100 g, respectively). The powder retained a significant quantity of phenolic compounds and antioxidant potential after sun-drying. The rheological evaluation indicated the dose-dependent incremental response on dough development and dough stability time. Although cupcakes prepared with purslane leaves and stem powder received lower ratings than the control, statistically, the cupcakes supplemented with 2 to 4% purslane powder were on par with each other. In conclusion, purslane leaves and stems are a rich source of micronutrients and their incorporation in bakery products can improve the consumer’s micronutrient intake.